Comparative phylogeographic patterns among selected indigenous and introduced Collembola on Marion Island - Myburgh, Marike (Stellenbosch : Stellenbosch University, 2006)
Thesis (MSc)--University of Stellenbosch, 2006. ENGLISH ABSTRACT: Marion Island is situated approximately 2600 km southeast of Cape Town and is the larger of the two islands that comprise the Prince Edward Island group. During past glaciation events, Marion was partially covered by ice with fauna and flora confined to isolated refugia across the island. As a result of these long-term isolation events, it is postulated that species predating these glaciation events might show geographic partitioning of genetic variation. Subsequently, the majority of Southern Oceanic islands have a history of sealing activities with vessels frequenting various islands in their hunt for seals. These combined visits to several islands could have facilitated the introduction of alien species, or the reintroduction of species already present on islands. These incidents, combined with more recent scientific voyages, have led to the establishment of several exotic species on Marion Island. Two indigenous Collembola species (Cryptopygus antarcticus (Willem, 1901) and Tullbergia bisetosa (Börner, 1903)) were chosen as model species to investigate the possible effects of glaciation on the spatial distribution of genetic variation on indigenous species. Given the negative impact that alien taxa have on indigenous species and ecosystems, the phylogeographic population structure of the recently introduced Isotomurus cf. palustris (Müller, 1876) was determined and compared to those described for the two indigenous species. To address these questions, two mitochondrial DNA genes were targeted: cytochrome oxidase subunit I (COI) and cytochrome oxidase subunit II (COII). These genes were sequenced (GENBANK accession numbers DQ147289-DQ147558) and analysed using, amongst others, AMOVA (Analysis of Molecular Variance), SAMOVA (Spatial Analysis of Molecular Variance) and NCA (Nested Clade Analysis). As expected, the two indigenous species showed distinct signs of population expansion, whilst the recently introduced species exhibits little genetic ...